De l’onomastique dans l’affirmation du sentiment national : le département oriental de San Martín au Pérou - Catherine Heymann (Caravelle)
Having followed law studies, the writer and well-known man, Jenaro Herrera (1861-1941), was born in the Peruvian Amazon, and published in 1918 a book dedicated to Peru’s north-oriental region : Legends and traditions of Loreto. In one of his traditions, he gives an explanation about the choice of San Martín to name an oriental department. This tradition was based upon a patriotic speech which shall be analyzed in this article, since it was the cause of a controversy between two major figures of Latin American Independence − San Martín and Bolívar.